Superior Vena Cava Syndrome in Men with Thymic Atypical Carcinoid (Neuroendocrine Tumor Grade 2) - Ramkita, Nora; Suly Auline Rusminan; Ika Kartika; Krisna Murti; S. Nurul Amanah Ratna Sari; Devi Eqtriana Setyaningsih (RSUP Dr Moh Hoesin Palembang, 2022)
Introduction: Cases of neuroendocrine tumors (NET) can occur in various organs, generally in the form of gastroenteropancreatic (GEP-NET) and pulmonary tract (PNET). The incidence of thymic neuroendocrine tumors (TNET) is rare, accounting for less than 5% of thymic and mediastinal malignancies, and 0.4% of all neuroendocrine tumors. Case presentation: A 57-year-old man came to RSUP Dr. Mohammad Hoesin Palembang with complaints of coughing, bluish and curved blood vessels in the chest, and shortness of breath during activities that have been getting worse for six months. CT scan showed a tumor measuring 18.6 x 11.7 x 11 cm in the anterior mediastinum and pressing on the superior vena cava and abdominal aorta. TTNA and core biopsy with CT guidance showed NET Grade 2, mitoses 6/2 mm2, positive tumor cells with immunohistochemistry for synaptophysin, chromogranin, CD 56, AE1/AE3, and Ki67 9%. The patient received paclitaxel and carboplatin chemotherapy for 6 cycles. Conclusion: The prognosis for atypical carcinoid patients is 20-80% for a 5-year survival rate. Appropriate patient management is needed to improve the outcome of patients with primary thymic atypical carcinoid (NET, grade 2).